BIODIESEL PRODUCTION FROM CORN OIL BY TRANSESTERIFICATION PROCESS - Khan, N. A.; Dessouky, H. (The Nucleus, 2020)
There is much political demand and economic pressure to convert agricultural surpluses into material, such as motor fuel, in which the world is deficient. Transport industry is primary consumer of crude oil. Due to scarcity of known petroleum reserves, the possible alternative fuel for use in present engine technology is biofuels. Europe, USA and Brazil are successfully using biofuels. Biofuels causes less environmental pollution as compared to normal petro fuels. As a fuel, ethanol (gasohol) is used in internal combustion engine while methyester (Biodiesel) is used in diesel engines with same or better performance as compared to petro fuels. Corn is very valuable crop with numerous industrial applications, and is used in more than 300 modern industries, including the manufacture of textiles, paper, adhesives, insecticides, paints, soaps, explosives and many more. Presently the biggest source of ethanol production is from corn (produced by USA). Edible oil can also be extracted from corn which is normally used for cooking and it can be used for biodiesel production. Many countries are experimenting on fats and oil to get feasible data for production of biodiesel. Presently USA prefer to use soybean oil as raw material for commercial production of biodiesel while in Europe rapeseed oil is preferred, so therefore, it depends upon the availability of raw material in particular area and may change from location to location. In Pakistan we started with corn oil to produce biodiesel by transesterification method. In present study different design parameters such as effect of temperature, catalyst concentration, molar ratio, and Stirrer speed were founded for better conversion of neat and used corn oil into biodiesel. The optimum parameters proposed for neat corn oil are 0.5% of catalyst based on weight of corn oil, temperature between 50o o C to 60 C, reaction time 15 minutes, molar ratio of 6:1 and speed of stirrer 155 rpm. In case of used corn oil high catalyst amount was used which was 0.7% based on the weight of oil. Fuel testing results of corn biodiesel was comparable with normal petro diesel fuel.